Plate tectonics and planetary convection - Kanasewich, E. R. (Canadian Journal of Earth Sciences, 1976)
A series of azimuthal–equidistant map projections, centered on each of the plates of lithosphere, is used to demonstrate the high degree of ordering and symmetry in the major plates. The Pacific and African plates are approximately circular with a radius of 60°. The entire pattern is dominated by these two major plates, exactly antipodal to one another in the form of a dipole. Between the two 'circular' plates is a ring of elliptical plates with irregular boundaries but a organized geometric interrelationship. The average major and minor axes of the 'elliptical' plates, measured at the center of the earth, are 62° ± 6 °and 30° ± 5°, and the major axes are oriented at angles of 56° ± 3 °to lines joining the center of the African plate. The centers of the 'elliptical' plates are arranged within 6° ± 3 °of a great circle path through the North pole. This organized distribution of the major plates is most likely the result of convection currents involving the entire mantle, from the lithosphere to the core. To a first approximation, the convective pattern may be modelled by a superposition of third order spherical harmonics, P 0 3 , P 1 3 , and P 2 3 in a pattern that regressed from a first spherical harmonic, −P 0 1 .